Analysis of the dependence of economic growth on electric power input and its influencing factors in China. (November 2021) - Xie, Pinjie; Li, Han; Sun, Feihu; Tian, Huizhen
Abstract: To realize the "Green" economic development, China has to transform the extensive mode of growth with the power factor inputs being the main driving force gradually into an intensive one. It's important to quantitatively analyze the relationship between the power factor input and economic growth and understand the core factors that affect the coordinated development between them. We introduce the concept of "power dependence, " based on the counter-factual method, use "growth drag" to reflect the dependence of China's economic growth on the power factor input. Based on the measurement of national power dependence, the auto-regressive distributed lag (ARDL) model is used to develop an empirical analysis of its influencing factors, and the robustness of the findings is tested by using the inter-provincial panel data. The findings show that China's economic growth has depended on the power factor input to some extent. According to the results, we propose suggestions from the aspects of promoting economic development, improving the pricing mechanism, adjusting the power generation structure, reasonably regulating the introduction of the foreign direct investment and research and development investment, and optimizing industrial structure to find an effective means to reduce the dependence of China's economic growth on the power factor input. Graphical abstract: Image 1 Highlights: Based on the growth drag model, the power dependence is measured. The integrated analysis of the influencing factors is based on ARDL. Verifying the robustness of conclusions by using inter-provincial panel data and GMM. Improving the power pricing mechanism is essential to affect the power dependence. Increasing the proportion of the service industry cannot reduce the power dependence.